EVALUASI TINGKAT KUALITAS KEPUASAN PASIEN PADA PELAYANAN INSTALASI FARMASI RUMAH SAKIT DIINDONESIA (Narrative Review) - Sukma, Sischa Milara; Wahyuningsih, Sri (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2024)
Good quality standards for health services are a level of perfection in health services, giving rise to a feeling of satisfaction in patients. This means that the more perfect the patient's satisfaction, the better the quality of health services. The aim of this review is to determine the level of patient satisfaction in hospital pharmacy installation services in Indonesia and to find out what factors influence the level of patient satisfaction in hospital pharmacy installations. . This review uses a narrative review which uses articles or journals published in 2014 -2024. The literature sources were obtained from the Google Scholar and Pud Med websites, namely 10 journals and were included in the inclusion criteria. The results obtained show that the friendliness of the staff, speed in administering medication, and comfortable facilities and infrastructure can increase patient satisfaction. In conclusion, the level of patient satisfaction is a reflection of the level of satisfaction in health services. The level of patient satisfaction is influenced by many factors, including the provision of drug information, the timeliness of drug administration services, the friendly attitude of staff, and the comfort of facilities and infrastructure which can increase patient satisfaction. Assessment of the quality of patient satisfaction services covers five main dimensions including: physical evidence, reliability, responsiveness, assurance and empathy.